ANALISIS PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN PSAP NO. 07 - Safitri, Rizkie Sari Indah; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTGovernment accounting in Indonesia is regulated in the Government Regulation of the Republic of Indonesia No. 71 of 2010 about the Accrual Based Government Accounting Standards. In the GAS there is the Statement of Government Accounting Standards (SGAS) No. 07 of Fixed Asset Accounting. This researchis meant to find out the fixed assets accounting treatment on the Department of Agriculture and Food Security of East Java which is compatible to the Statement of Government Accounting Standards (SGAS) No. 07. The data analysis method has been carried out by using descriptive method. The data is the primary and secondary data. The data collection techniques has been done by performing observation, documentation and interview.The result of the research showsthat fixed asset accounting treatment at the Department of Agriculture and Food Security of East Java province which covers Recognition, Termination and Release, as well as the disclosures in the period of 2011-2014 can be concluded that it is in conformity with the provisions of the Statement of Government Accounting Standards (PSAP) No. 07. However, the accounting treatment for fixed assets depreciation it is currently in conformity with the SGAS in 2014 periods.Keywords: government accounting, SGAS No. 07, fixed assets.